Tunable external cavity diode lasers - Ye, Cunyun, 1965- (World Scientific, 2004)
Annotation - Presents a thorough account of the state-of-the-art of tunable external cavity diode lasers Provides an up-to-date survey on physics, technology, and performance of widely applicable coherent radiation sources of tunable external cavity diode lasers May be used as a textbook for related undergraduate and graduate courses.
Keywords: Semiconductor lasers.; Diodes, Semiconductor.; elektronické knihy; electronic books